Some features of legal regulation of higher and postgraduate education in Kazakhstan and the USA - Галиакбарова, Гузаль (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The education system in Kazakhstan has been continuously developing since independence, with each passing year gaining new momentum and setting itself certain tasks towards the formation of a national model of education, including higher and postgraduate education, aimed at improving the quality of training of human resources, meeting the needs of the individual, society, and the state. The research aims to conduct a comparative analysis of the legal regulation of higher and postgraduate education in Kazakhstan and the United States. The scientific significance lies in a comprehensive analysis of the legal regulation of higher and postgraduate education in Kazakhstan and the United States. The practical significance is to develop proposals for improving the Kazakh legislation in the field of higher and postgraduate education based on the best practices of the United States. The research was conducted using the method of comparative legal analysis, formal-logical, historical legal, and system-analytical methods. The value of the research lies in its provision of a comprehensive overview of the legal regulation of higher and postgraduate education in Kazakhstan and the United States. The research results can be used to improve Kazakh legislation and develop programs for the development of higher and postgraduate education.